DINAMIKA SPASIAL PEMANFAATAN LAHAN OLEH MASYARAKAT DAERAH ALIRAN SUNGAI (DAS) KREO - Setyowati, Dewi Liesnoor (Forum Ilmu Sosial, 2009)
Landuse dynamics of Kreo watershed from the result of interpretation of satellite image landsat (the year 1994) and image SPOT-5 (the year 2006) in the form of degradation of open farm wide of 67,07%, coppice 9,61%, forest 6,69%, and rice feld 4,64%; improvement of plantation wide 24,42%, setlement 21,68%, and mixture garden with a width of 1,05%. Forest wide and plantation of DAS Kreo only with a width of 17,19% had not pursuant to ideal wide of minimum forest of 30% at one particular in watershed (PP number 33 the year 1970). Wide area of setlement in Kreo watershed with a width of 12,21% is including category has exceeded ideal boundary of setlement area at one particular in watershed, maximum boundary (threshold) in the form of area of waterproof equal to 6%-10% in watershed.Keywords: Landuse spatial dynamic, landuse trend.